Job mobility among high-skilled and low-skilled teachers - Krzysztof Karbownik (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
This paper examines the job mobility of teachers with different skills using matched employer-employee data from Swedish secondary schools. In addition to standard quality measures, I have access to population-wide data on cognitive and non-cognitive assessments of males born in 1951 or later. The results show that high-quality teachers are less mobile than others, and that there is no significant correlation between turnover and share of minority students. Interestingly, teachers with better skills are less likely to leave the profession, which suggests that the documented drop in the quality of inflowing teachers may partly be offset by a higher tendency for high quality teachers to stay in the profession.
Keywords: I21; J44; 330; teacher turnover; teacher quality; student composition